Patient Perceptions of Service Quality at dr. Charles P.J. Suoth Lanud Sam Ratulangi Hospital Using the Importance Performance Analysis (IPA) Method - Syahwildan, Mhd.; Rohendi, A; Rahim, Agus Hadian (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study examined patient perceptions of service quality at dr. Charles P.J. Suoth Lanud Sam Ratulangi Hospital using the Importance Performance Analysis (IPA) method integrated with Servqual. A qualitative descriptive research design was employed, involving 38 inpatients selected through double sampling. Five service quality dimensions were evaluated: Tangibles, Reliability, Responsiveness, Safety, and Empathy. Servqual analysis revealed that negative gap values predominated across 19 of 27 attributes, with the Empathy dimension recording the largest mean gap (−0.25). IPA quadrant mapping identified six attributes requiring immediate improvement, four to be maintained, five of low priority, and twelve exceeding patient expectations. Improvement strategies are recommended in three domains: physical facility expansion, staff communication training, and service timeliness enforcement. The findings underscore the centrality of interpersonal dimensions—particularly Empathy and Responsiveness—in shaping overall patient satisfaction in military hospital settings.